“Someone Kept Sacrificing”: Disentangling Gender Ideology in Immigrant Narratives of Social Reproduction. - Hari, Amrita (Signs: Journal of Women in Culture & Society)
“Doing gender,” the concept proposed by Candace West and Don H. Zimmerman in 1987, has been criticized on two fronts: first, it leaves little room for gender to be undone; second, it fails to recognize the systemic factors that contribute to the maintenance of gender inequality. A host of feminist studies in the 1980s and 1990s established migration as a catalyst to undo gender, in that migration tends to disrupt conventional gender roles and to enable gender-atypical work-family arrangements. This study draws on the narratives of forty-two heterosexual partnered immigrants of Indian origin, living in Canada, whom I asked about their engagement with the Canadian labor market and about their gendered division of household labor. I found that this group of newcomers are not undoing gender and becoming more gender egalitarian after migrating, as earlier studies suggested they might. They experience racial discrimination in the Canadian labor market, thus destabilizing their career trajectories and making them realize that their buying power is lower in Canada, which influences them to take gender-typical paths to negotiate social reproduction. The article concludes with a call for a more race-, class-, and gender-conscious account of gender ideology in different postmigratory contexts.